Balancing Proliferation with Igκ Recombination during B-lymphopoiesis - Hamel, Keith M.; Mandal, Malay; Karki, Sophiya; Clark, Marcus R. (Frontiers in Immunology, 2014)
The essential events of B-cell development are the stochastic and sequential rearrangement of immunoglobulin heavy (Igμ) and then light chain (Igκ followed by Igλ) loci. The counterpoint to recombination is proliferation, which both maintains populations of pro-B cells undergoing Igμ recombination and expands the pool of pre-B cells expressing the Igμ protein available for subsequent Igκ recombination. Proliferation and recombination must be segregated into distinct and mutually exclusive developmental stages. Failure to do so risks aberrant gene translocation and leukemic transformation. Recent studies have demonstrated that proliferation and recombination are each affected by different and antagonistic receptors. The IL-7 receptor drives proliferation while the pre-B cell antigen receptor, which contains Igμ and surrogate light chain, enhances Igκ accessibility and recombination. Remarkably, the principal downstream proliferative effectors of the IL-7R, STAT5 and cyclin D3, directly repress Igκ accessibility through very divergent yet complementary mechanisms. Conversely, the pre-BCR represses cyclin D3 leading to cell cycle exit and enhanced Igκ accessibility. These studies reveal how cell fate decisions can be directed and reinforced at each developmental transition by single receptors. Furthermore, they identify novel mechanisms of Igκ repression that have implications for gene regulation in general.